PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DI FAVEHOTEL OLO PADANG - Helfi, Vella Novita (journal of residu, 2019)
This study aims to determine the effect of job satisfaction on employee turnover intentions at Favehotel Olo Padang. This type of research is classified as associative quantitative research with a simple linear regression test. The population in this study were all employees at Favehotel Olo Padang. The research sample amounted to 38 employees with the sampling technique is saturated sampling. The technique of data collection is done using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Data were analyzed by simple linear regression testing through the help of the SPSS Computer Program version 16.00. The results showed: 1) Employee job satisfaction at Favehotel Olo Padang agreed, namely 50%, 2) Turning intention into the category of agree and disagree (39.47%), 3) there is a significant influence between job satisfaction and turnover intention with value constant of 106,783 and regression coefficient of 0.443 with a significance value of 0.005.